Meropenem pharmacokinetics during relapsing peritonitis due to ESBL‐producing Enterobacteriaciae in a liver transplant recipient - Kensuke Shoji; Jumpei Saito; Yusuke Oho; Shotaro Matsumoto; Satoshi Aoki; Akinari Fukuda; Seisuke Sakamoto; Mureo Kasahara; Edmund Capparelli; Isao Miyairi (Clinical Case Reports, 2019)
Abstract We report on an 8‐year‐old girl with Wilson disease who developed three episodes of peritonitis due to extended‐spectrum beta‐lactamase‐producing Escherichia coli after liver transplantation. Massive ascites were thought to account for low meropenem concentrations with standard dosing. Extending the infusion achieved higher troughs, greater time above minimum inhibitory concentration.